Not All That Masses Are Cancer: Pilomatrixoma Presenting as Breast Cancer - Özkara, Murat; Çimen, Şebnem; Hıdıroğlu, Mehmet Mert (The European Research Journal, 2026)
Pilomatrixoma is a rare benign skin neoplasm originating from the hair follicle matrix and is exceptionally uncommon in breast tissue, particularly in male patients. Due to overlapping clinical and ultrasonographic features, it is frequently misdiagnosed as breast cancer. This study aims to highlight pilomatrixoma as an important differential diagnosis of breast masses and to emphasize the role of histopathological confirmation. We report two male patients with breast lesions. A 40-year-old male presented with an infected breast lesion, and a 70-year-old male presented with a palpable breast mass. Both patients underwent clinical evaluation, ultrasonography, and tru-cut biopsy. Following histopathological confirmation of pilomatrixoma, elective surgical excision was performed. Tru-cut biopsy findings in both cases were consistent with pilomatrixoma. Ultrasonographic evaluation suggested suspicious features, leading to BI-RADS 4–5 categorization and initial concern for malignancy. Complete surgical excision with clear margins was achieved in both patients, and no complications or recurrences were observed. Pilomatrixoma is a rare benign tumor of the skin that can closely mimic breast cancer, especially on imaging. Despite its typical occurrence in the head, neck, and upper extremities and predominance in young females, it should be considered in the differential diagnosis of male breast masses. Histopathological confirmation via tru-cut biopsy is essential for accurate diagnosis, and surgical excision with clear margins is curative.